Association of Radioiodine for Differentiated Thyroid Cancer and Second Breast Cancer in Female Adolescent and Young Adult - Zhao, Xianlan; Chen, Mingjing; Qi, Xiaojing; Zhu, Haizhen; Yang, Guangrong; Guo, Yi; Dong, Qiang; Yang, Qiao (Frontiers in Endocrinology, 2022)
Background: Exposure to radiation is related to breast cancer occurrence. While whether the radioiodine (RAI) increases the risk of second breast cancer (SBC) in female differentiated thyroid cancer (DTC) patients is not well addressed. Methods: All patients were identified from Surveillance, Epidemiology, and End Results database. At least a 5-year latency was guaranteed since exposure to RAI. Fine and Gray model was used to calculate the cumulative incidence and hazards ratios (HR) and 95% confidence interval (CI). Standardized incidence ratio (SIR) was calculated by Poisson regression analysis. Propensity score matching was used for match analysis. Survival analyses were performed by the Kaplan-Meier method and the log-rank test. Results: A total of 406 out of 16850 patients in the RAI group and 733 out of 22135 patients in the no RAI group developed SBC. The cumulative incidences of SBC were higher in patients with RAI compared to patients without RAI in the adolescent and young adult (AYA) group and the middle-aged adult group. In the AYA group, patients with RAI had increased HR (1.65, 95% CI 1.33-2.05, P < 0.001) compared to those without RAI, and the HR increased slightly with latency. In addition, the SIR (1.21, 95% CI 1.02-1.44, P < 0.05) increased compared to the general population. While in the middle-aged adult group, only a slightly higher HR (1.18) was found. The survival after SBC was inferior to those with matched only primary breast cancer. Conclusions: RAI treatment increased the risk of SBC in female AYA DTC patients. A long-term follow-up should be performed in this population.